Delayed stent implantation following primary percutaneous coronary intervention for ST elevation myocardial infarction in patients with severe massive thrombus. (12th October 2011) - Yin, Da; Zhu, Hao; Zhou, Xuchen; Jia, Yuqing; Cui, Hashen; Sun, Shise
Abstract : Objective: To compare the two strategies, Delayed-Stent implantation and conventional-stent implantation (routine procedure), for ST elevation myocardial infarction (STEMI) in patients with massive thrombus burden following Primary Percutaneous Coronary Intervention. Methods: From August 2009 to March 2011, 90 out of 172 consecutive STEMI patients with massive thrombus burden were involved. All the patients achieved TIMI grade 3 flow and residual stenosis <50%, post thrombus aspiration and plain old balloon angioplasty. It randomised to delayed-stent implantation group (D group, 45 patients) and conventional-stent implantation group (C group, 45 patients). Corrected TIMI Frame Count (cTFC), myocardial blush grade (MBG), Ratio of ST fall-after-rise >70% within 24 h, massive haemorrhage, major adverse cardiac event (MACE) in hospital and 30 days follow-up were assessed. Results: Compared with C group, D group achieved better results in cTFC (24.51±6.38 vs 32.13±8.96, p=0.026), MBG (2.24±0.93 vs 1.72±1.12, p=0.02), the ratio of no-reflow (7.70% vs 31.53, p<0.001), ST fall-after- rise>70% within 24 h (81.23% vs 71.67%, p=0.002). However, massive haemorrhage, in-hospital and 30-day follow-up MACE were no difference. Conclusion: Compared with conventional PCI, the strategy of delayed-stent implantation is a rational and feasible choice for STEMI in Patients with Massive Thrombus Burden.